Does primary tumor localization has prognostic importance in seminoma patients?: Turkish Oncology Group Study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2020)
Purpose: The purpose of this study was to determine whether primary tumor localization may be a risk factor for relapse and survival in seminomatous germ cell tumors (GCT) patients. Methods: In our study, 612 seminomatous GCT patients diagnosed in 22 centers between 01.01.1989 and 03.02.2019 were retrospectively evaluated. Patient interview information, patient files and electronic system data were used for the study. Results: The primary tumor was localized in the right testis in 305 (49.9%) patients and in 307 (50.1%) in the left testis. Mean age of the patients was 36 years (range 16-85 +/- 10.4). The median follow-up period was 47 months (1-298). Recurrence was observed in 78 (127%) patients and 29 (4.7%) died during the follow-up period. Four-year overall survival (OS) was 95.4% and 4-year progression-free survival (PFS) was 84.5%. The relationship between localization and relapse was significant in 197 patients with stage 2 and stage 3 (p=0.003). In this patient group, 41 (20.8%) relapses were observed. Thirty (73.2%) of the relapses were in the right testis and 11 (26.8%) in the left testis. Four-year OS was 92.1% in patients with right tumor; and 98.7% in patients with left tumor (p=0.007). When 612 patients were evaluated with a mean follow-up of 4 years, there was a 6.6% survival advantage in patients with left testicular tumor and this difference was significant (p=0.007). Conclusion: Survival rates of patients with primary right testicular localization were worse compared with left testicular localization, and relapse rates were higher in stage 2 and 3 patients with right testicular localization.
Keywords: testicular cancer; germ cell tumor; seminoma; primary tumor localization; prognosis; survey; SURVEILLANCE FOLLOWING ORCHIECTOMY; EUROPEAN CONSENSUS CONFERENCE; RISK-ADAPTED TREATMENT; GERM-CELL-CANCER; STAGE-I SEMINOMA; TESTICULAR CANCER; DIAGNOSIS; PATTERNS; RELAPSE